Value Added Tax reforms and tax compliance among Small and Medium Enterprises in Nairobi, Kenya: moderated by taxpayer behavior - Wairimu, N. K. (Strathmore University, 2025)
Tax compliance remains a challenge for Small and Medium Enterprises in Nairobi, despite Value Added Tax reforms and taxpayer education, with Kenya’s Value Added Tax compliance gap averaging 40%, resulting in an annual loss of KES 200 billion due to tax evasion and inefficiencies. This study’s main objective was to examine the effect of Value Added Tax reforms and taxpayer education on Value Added Tax compliance among Small and Medium Enterprises, while also assessing the moderating role of taxpayer behavior. The study’s specific objectives were to examine the effect of Value Added Tax reforms and the effectiveness of taxpayer education programs on VAT compliance among small and medium enterprises in Nairobi, while also assessing how taxpayer behavior moderates the relationship between Value Added Tax reforms, taxpayer education, and Value Added Tax compliance. The study was guided by deterrence theory and the slippery slope framework theory, employing a positivist research philosophy and a quantitative descriptive research design. The target population was 2,416,368 Small and Medium Enterprise owners and employees in Nairobi. Using Slovin’s formula, a sample of 200 SMEs across wholesale, retail, manufacturing, and services was selected proportionally. Data was collected via structured questionnaires, both online and in hard copy, following ethical guidelines to ensure confidentiality and academic use only. Data analysis involved data cleaning, coding, and applying ordinal logistic regression to examine the effects of Value Added Tax reforms, taxpayer education, and taxpayer behavior on Value Added Tax compliance. The study found that while VAT reforms like eTIMS and auto-populated returns aimed to simplify compliance, they often introduced new challenges such as system unreliability and increased compliance costs. Taxpayer education, though mostly delivered digitally, was found to be less effective for SMEs who preferred on-ground, sector-specific training that allowed real-time engagement. Additionally, taxpayer behavior significantly influenced compliance, with SMEs showing higher compliance when they had positive attitudes toward reforms and adopted proactive tax practices. This highlights the importance of behavioral alignment in policy design. The study contributes to the growing literature on VAT compliance by integrating the moderating role of taxpayer behavior in Kenya’s context and recommending more inclusive, user-friendly reforms and educational strategies. However, the study is limited by its focus on Nairobi SMEs and a lack of long-term analysis, suggesting the need for future research on regional differences and the sustained effects of reforms and education. Key Words: Value Added Tax (VAT), VAT Reforms, Taxpayer Education, Taxpayer Behavior, Tax Compliance.
Full - text thesis